Chief Executive Officer duality and company performance: a case of Malaysian companies - Said, Roshima; Yaacob, Zuraini; Awang, Norasmila; Ismail, Jurina; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2009)
The concept of the agency theory and the stewardship theory had a different point of view on what constitute a good governance practice in the public firms. The agency theory believed that the separation of Chief Executive Officer and board chair roles is necessary to reduce the managers’ opportunistic behaviors which could reduce the shareholders’ wealth. In contrast the stewardship theory believed that Chief Executive Officer duality promotes flexibilities and reduce conflicts of interest between the boards of directors and management, which in turn lead them to perform effectively and efficiently. The objective of this paper is to examine the relationship between Chief Executive Officer duality and companies’ performance of Malaysian public listed companies for the year ended 2002. Particularly, the study wants to examine whether the performance of the company is determined by the leadership structure of duality or independent leadership status. The findings of the study showed that companies with independent leadership showed a better performance in term of the proportion of return on asset to leverage (ROE) and profit after tax and interest to sales (profit margin) as compared to the Chief Executive Officer duality companies, the difference is however, not statistically significant. Therefore, the study explained that the separation of the roles of Chief Executive Officer and chairperson does not necessarily contribute to a better performance and that the duality issue is not a contributing factor in determining the performance of a company. The study will help the main board of directors of the company to gain information regarding corporate governance. The separation of CEO and board Chairman is important as it provides independence in board decision and therefore, is believed to avoid corporate abuse and other ineffective governance practice implies that the separation of the roles of Chief Executive Officer and Chairman does not necessarily contribute to a better performance of the companies. For further research it is suggested a companies listed on Kuala Lumpur Stock Exchange Main Board and Second Board.